Clinical and genetic heterogeneity of neonatal diabetes mellitus (review of the literature) - Tamara Leonidovna Kuraeva; Andrey Olegovich Emel'yanov (Сахарный диабет)
Diabetes mellitus detected within the first 6 months of life is termed neonatal diabetes. Two its forms, permanent and transient, differ in the durationof insulin dependence. The review contains data on mechanisms underlying this pathology and its specific clinical features.